Combination of Polydopamine Coating and Plasma Pretreatment to Improve Bond Ability Between PEEK and Primary Teeth - Teng, Rui; Meng, Yuchen; Zhao, Xiaodan; Liu, Jie; Ding, Rui; Cheng, Yilong; Zhang, Yunhe; Zhang, Yanfeng; Pei, Dandan; Li, Ang (Frontiers in Bioengineering and Biotechnology, 2021)
Preformed crowns are preferred to reduce the failure risk of restoration of primary teeth, but some drawback of conventional material is still a main barrier for their clinical use. Polyether etherketone (PEEK), a tooth colored, high-performance thermoplastic polymer, has been recognized as a promising alternative to manufacture the restoration of primary teeth. However, the hydrophobic surface and low surface energy of PEEK make it hard to establish a strong and durable adhesion. In this study, we have evaluated a modification method of polydopamine (PDA) coating with plasma pretreatment for the PEEK films by physical and chemical characterization, bonding properties, and biocompatibility. The surface properties of PEEK were well-characterized by scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS). The adhesive strength of the PEEK films was greatly improved without significant reduction of the proliferation rate of human gingival fibroblast cells in MTT and Live/Dead assays. Therefore, PDA coating with plasma pretreatment may give a new solution for effective clinical application of PEEK in primary performed crowns.